Measuring Efficiency Gains of Fuel Substitution in Thermal Power Generation - Peykanfar, Arash (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
As the global population and affluence increase, electricity demand will increase accordingly. Although pressure from the international community due to increased environmental awareness has led to a surge in the use of clean and renewable sources for electricity generation over the past decade (especially in developed countries), over half of the world’s electrical energy used today is from steam turbine generators burning fossil fuels, with large scale fossil-fueled plants providing most of the world’s baseload generating capacity. Meanwhile, many thermal power plants worldwide- mostly in undeveloped countries - are inefficient and can be optimized financially and economically and minimize their environmental impact. Fuel flexibility and choosing the correct type of thermal plant appropriate to the forecast load can be considered in maintaining power generation efficiency. This study aims to undertake a Cost-Effectiveness analysis (CEA) of two different power generating technologies - Internal Combustion (Diesel) and combined cycle gas turbines – in the Turkish Republic of North Cyprus (TRNC) by analyzing the appropriateness of using heavy fuel oil (HFO) and liquefied natural gas (LNG) to ascertain an economically optimum combination, nonetheless, could be extended to any other place with the appropriateness of these types of plants.

ÖZ: Küresel nüfus ve refah arttıkça, elektrik talebi de buna bağlı olarak artacaktır. Artan çevre bilincine bağlı olarak uluslararası toplumdan gelen baskı, geçtiğimiz on yılda (özellikle gelişmiş ülkelerde) elektrik üretimi için temiz ve yenilenebilir kaynakların kullanımında bir artışa yol açsa da, bugün kullanılan dünya elektrik enerjisinin yarısından fazlası buhardan sağlanmaktadır. fosil yakıtları yakan türbin jeneratörleri ve dünyanın temel yük üretme kapasitesinin çoğunu sağlayan büyük ölçekli fosil yakıtlı tesisler. Oesnada, dünyanın her yerinde, çoğu gelişmemiş ülkelerde çalışan birçok termik santral verimsizdir ve finansal, ekonomik ve çevresel etkilerini en aza indirgemek için optimize edilebilir. Yakıt esnekliği ve tahmini yüke uygun doğru termik santral tipinin seçilmesi, enerji üretim verimliliğinin korunmasında düşünülebilir. Bu çalışma, Kuzey Kıbrıs Türk Cumhuriyeti'nde (KKTC) iki farklı güç üretim teknolojisinin - İçten Yanmalı (Dizel) ve kombine çevrim gaz türbinlerinin - Maliyet Etkililik analizini (CEA), ağır akaryakıt kullanımının uygunluğunu analiz ederek gerçekleştirmeyi amaçlamaktadır. HFO) ve sıvılaştırılmış doğal gaz (LNG), ekonomik olarak optimum bir kombinasyonu belirlemek için, yine de, bu tür tesislerin uygunluğuyla başka herhangi bir yere genişletilebilir.
Master of Science in Energy Economics and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Economics Department; Energy Economics and Finance; Power--Energy--Heat--Transmission; Steam power plants; Electric power systems; Energy Production--Economics--Thermal Power Generation--Cyprus (Turkish Republic of Northern Cyprus, 1983-); AElectricity Production--Electricity Generations--Economics; Electricity generation, efficiency, CEA, fuel flexibility, thermal power generation, diesel, TRNC, CCGT, HFO, LNG